2010
DOI: 10.1017/s002238160999051x
|View full text |Cite
|
Sign up to set email alerts
|

Legislative Success in a Small World: Social Network Analysis and the Dynamics of Congressional Legislation

Abstract: We examine the social network structure of Congress from 1973 to 2004. We treat two Members of Congress as directly linked if they have cosponsored at least one bill together. We then construct explicit networks for each year using data from all forms of legislation, including resolutions, public and private bills, and amendments. We show that Congress exemplifies the characteristics of a ''small world'' network and that the varying small-world properties during this time period are related to the number of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(44 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…This finding accords with previous studies demonstrating that intra-party cooperation is influenced by representatives' perceptions about different values for different issues and the internal distribution of power within the party (Pedersen 2010;Crisp & Driscoll 2012). However, in daily parliamentary life representatives do use various cooperative strategies depending on the interests they want to advance (Tam-Cho & Fowler 2010;Marangoni & Tronconi 2011).…”
Section: Findings and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding accords with previous studies demonstrating that intra-party cooperation is influenced by representatives' perceptions about different values for different issues and the internal distribution of power within the party (Pedersen 2010;Crisp & Driscoll 2012). However, in daily parliamentary life representatives do use various cooperative strategies depending on the interests they want to advance (Tam-Cho & Fowler 2010;Marangoni & Tronconi 2011).…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The results strengthen previous studies regarding the use of sponsorship as a way to cooperate with colleagues during the legislative process (e.g., Campbell 1982;Koger 2003;Rocca & Sanchez 2008). The cooperative strategies model posits three situations under which legislators will cooperate: to meet the demands of their constituency, to advance the goal of being re-elected or in response to social networking (Kiiver 2006;Tam-Cho & Fowler 2010). Hence, we can say that the decision to cooperate with others is based mainly on the desire to achieve the goals framed previously.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the work on collaborative relationships in legislatures has focused either on how individual factors influence relational formation (Desmarais, Cranmer, and Fowler ; Bratton and Rouse ; Gross and Shalizi ) or on how the patterns and positions of relationships in the legislative network influence outcomes (Fowler ; Tam Cho and Fowler ). These works have consistently shown that (1) relationships between legislators form in structured, predictable ways and (2) that the network of relationships between legislators has important implications for legislating.…”
mentioning
confidence: 99%